Perceptions among diabetic patients in the ultra-orthodox Jewish community regarding medication adherence: a qualitative study - Inbar Levkovich; David Rodin; Shiri Shinan-Altman; Mordechai Alperin; Hodaya Stein (BMC, 2021)
Abstract Background Promoting a healthy lifestyle and achieving strict adherence to medical treatment among patients with diabetes are key objectives in public health. Yet health behaviors are often culturally driven, especially in closed religious communities. This study seeks to reveal key cultural-religious factors, attitudes and behaviors characterizing the lifestyle in one such closed community-the ultra-Orthodox Jewish community-by understanding the attitudes of ultra-Orthodox patients with diabetes toward coping with their illness and the factors impacting their adherence to medicinal treatment. Method Qualitative interviews were conducted with 16 ultra-Orthodox patients with diabetes using a semi-structured, in-depth questionnaire. Results Three main themes emerged: 1) "The disease as a secret": Hiding the disease among patients with diabetes in ultra-Orthodox society; 2) "Distinguishing between sacred and secular occasions": ultra-Orthodox diabetes patients distinguish between treatment adherence on weekdays and treatment adherence on holidays or special occasions; 3) "Ask the rabbi": In cases of dilemmas that involved conflicts between halakhic rulings and doctors' instructions, the rabbi's decision was usually the final one. Conclusions The findings of this study may help provide an in-depth understanding of the obstacles and motives of ultra-Orthodox patients in adhering to medicinal treatment of diabetes in particular and to medicinal treatment in general, thus helping family physicians who treat this population provide optimal and appropriate treatment.